Global Aging Pressures : Impact of Fiscal Adjustment, Policy Cooperation, and Structural Reforms - Kumar, Manmohan (IMF Working Papers; Working Paper, 2007)
Demographic pressures will materialize in many economies over the next few decades. We examine the macroeconomic impact of alternative fiscal adjustment and structural reform strategies to address these global aging pressures using the IMF's Global Fiscal Model (GFM). The results suggest substantial spillover effects of aging through international financial channels. To maintain sustainability, fiscal adjustment needs to be broad-based, while avoiding increases in direct taxes. There are substantial benefits from fiscal cooperation, while negative growth effects can be offset by complementary structural reforms in product and labor markets with the benefits accruing early and to all incomegroups.